THE ANALYSIS OF CULTURE SHOCK EXPERIENCED BY ERIN GRUWELL IN FREEDOM WRITERS (2007) MOVIE - Junaid, Syahruni; Andini, Citra; Satria, Satria; Alwi, Widyawati; Amalia, Ainy Nur (Journal of Islamic Culture and Literature (JICeL), 2025)
This research aimed at finding out the phases, effects, causes of culture shock experienced by Erin Gruwell as well as her strategies to overcome it. The research method used was descriptive qualitative method. The data were taken from Freedom Writers experienced by the main character, Erin Gruwell. Based on the results of the research, it shows that there are four phases of culture shock experienced by Erin Gruwell in Freedrom Writers namely the honeymoon Phase, the crisis phase, the recovery phase, the adjustment phase. The writer also found two causes of culture shock experienced by the character Erin Gruwell namely student factors and Injustice of School and Teaching Teams. Morover, the result shows that there are two affects that is appeared through the phases of culture shock, they are the positive effects includes better awareness and empathy, forcing herself to innovate in teaching, self confidence, and building realtionship with her students and negative effects including stress and emotional burden, personal sacrifice, and financial challenges. Furthermore, there are several stategies that Erin used, namely understanding and emphaty, innovation in teaching method, and collaborative approaches. Keywords: Culture shock, teaching, racial conflict, Movie